PENGEMBANGAN MEDIA E-LEARNING BERBASIS MOODLE SEBAGAI SUPLEMEN PEMBELAJARAN GEOGRAFI PADA MATERI MITIGASI BENCANA ALAM - Raffi Mariezki; Erna Juita; Momon Dt Tanamir (JAMBURA GEO EDUCATION JOURNAL, 2021)
This study aims to analyze the feasibility and practicality of moodle-based e-learning as  supplement to learning geography in natural disaster mitigation materials. This type of research is research and development of the four d model, namely: Define, Design, Development, Desiminate. The research subjects of SMA N 3 Padang class XI IPS. Moodle-based e-learning development includes validation of media, education and language experts. The validation data were processed using the interclass correlation coefficient and the results obtained were 0.957. If the value is more than 0.5, it can be concluded that the level of validation is adequate. Measurement of the feasibility of the media is obtained from data processing using Microsoft Excel so that a total score of 282 is obtained with a mean of 4.90 and a percentage of 98% with a very good predicate. The practicality test of moodle-based e-learning media was based on questionnaire data and obtained a total score of 4077 with a mean of 4.1 and a percentage of 82% with the very practical category.